2018
DOI: 10.1039/c7nr08979a
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale dewetting assembly of gold nanoparticles for plasmonic enhanced upconversion nanoparticles

Abstract: Plasmonic nanostructures have been broadly investigated for enhancing many photophysical properties of luminescent nanomaterials. Precisely controlling the distance between the plasmonic nanostructure and the luminescent material is challenging particularly for the large-scale production of individual nanoparticles. Here we report an easy and reliable method for the large-scale dewetting of plasmonic gold nanoparticles onto core-shell (CS) upconversion nanoparticles (UCNPs). A commensurate NaYF4 shell with a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 44 publications
(47 reference statements)
1
24
0
1
Order By: Relevance
“…Apart from sensitizing ion doping, significant progresses have also been made for improving the up-conversion luminescence of Er 3+ ions in rare-earth nanocrystals through surface passivation by forming core-shell structures (Yi and Chow, 2007 ; Fan et al, 2019 ), surface plasmon coupling by conjugating to noble metal particles (Sun et al, 2014 ; Clarke et al, 2018 ), and host-lattice manipulation by non-lanthanide (Ln) ions doping (Dong et al, 2013 ). The epitaxial growth of a shell on preformed emitting core, e.g., growing NaGdF 4 shell on NaGdF 4 :Yb,Er core (Vetrone et al, 2009 ; Li et al, 2013 ), can suppress the energy transfer from the emitting core to surrounding environment, thus favorable for boosting the luminescence efficiency, apart from giving rise to stable and controllable core/shell structures (Wang et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from sensitizing ion doping, significant progresses have also been made for improving the up-conversion luminescence of Er 3+ ions in rare-earth nanocrystals through surface passivation by forming core-shell structures (Yi and Chow, 2007 ; Fan et al, 2019 ), surface plasmon coupling by conjugating to noble metal particles (Sun et al, 2014 ; Clarke et al, 2018 ), and host-lattice manipulation by non-lanthanide (Ln) ions doping (Dong et al, 2013 ). The epitaxial growth of a shell on preformed emitting core, e.g., growing NaGdF 4 shell on NaGdF 4 :Yb,Er core (Vetrone et al, 2009 ; Li et al, 2013 ), can suppress the energy transfer from the emitting core to surrounding environment, thus favorable for boosting the luminescence efficiency, apart from giving rise to stable and controllable core/shell structures (Wang et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…This unique property of plasmonic nanostructures can alter certain properties of nearby molecules/emitters, and thus has been applied in many ways, such as chemical and biological sensors and plasmon‐enhanced spectroscopies (e.g., surface‐enhanced Raman scattering). [ 4 ] For the plasmon‐modulated UCL emission, numerous strategies to engineer UCNP‐plasmon geometry have been developed, via the fabrication of plasmonic satellite and core–shell structures, [ 5 ] random extended structures, [ 6 ] or single particle manipulation (e.g., by atomic force microscopy). [ 7 ] As is known, the LSPR frequency, spatial arrangement and distance between the emitters and plasmonic structures exert great impact on the outcome of plasmonic modulation.…”
Section: Figurementioning
confidence: 99%
“…Recent reports reveal that the upconversion luminescence can be efficiently enhanced by coupling UCNPs with plasmonic metal nanostructures . Due to the emission and absorption band match between the UCNPs and surface plasmon in grating nanohole array, nanoparticle and photonics crystal, the upconversion intensity can be dramatically enhanced by several to thousand folds . Lu et al reported a nanosilver grating which couples efficiently with UCNPs and got an enhancement factor of 16 for the green emission under the excitation of 1 kW cm −2 .…”
Section: Introductionmentioning
confidence: 99%